MODELING SUPPLY CONTRACTS TO MANAGE OUTSOURCING RISKS OF LOGISTICS' ACTIVITIES - Narulidea, Winda; Wijaya, Sekarsari Utami (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2018)
Many companies managed to improve logistics performance by making outsourcing decisions on logistics activities. The use of logistics outsourcing, not only can maintain their focus on core businesses, but also continue to minimize distribution costs by establishing relationships with third party service providers to create value of their operational performance excellence. But in a decentralized supply chain condition, the control of the supply chain players towards third-party logistics service providers is also limited, while the performance of logistics services affects the availability of products, quality, price, and market share of these companies. Coordination mechanisms are needed in a decentralized supply chain, especially with the implementation of logistics outsourcing decisions, so companies can maintain competitive advantage. In this paper, the model revenue and inventory-risk sharing contract was developed to coordinate the supply chain consisting of manufacturers, third party logistics service providers, and retailers. In addition, incentive and penalty schemes are applied based on the performance of logistics service providers that will affect the level of availability in retailers, so that inventory risk can also be allocated to all stakeholders.